Analisis Penerapan Good Governance dalam Pelaksanaan Program Makan Bergizi Gratis (MBG) pada Siswa Sekolah - Feni Huspita Sari; Ade Uswatun Hasanah; Sutinah Andaryani (SENTRI: Jurnal Riset Ilmiah, 2026)
The Free Nutritious Meal Program (MBG) is one of the Indonesian government's strategic initiatives aimed at improving the nutritional status, health, and learning outcomes of school students. The successful implementation of this program depends not only on the availability of funding and effective food distribution but also on the application of good governance principles, including transparency, accountability, participation, effectiveness, and coordination among stakeholders. This study aims to analyze the implementation of good governance principles in the Free Nutritious Meal Program and identify the challenges that affect its effectiveness. The study employs a qualitative approach using a literature review method by examining relevant academic publications, government policy documents, and previous research related to public governance and nutrition programs. The findings indicate that the implementation of good governance principles in the MBG program continues to face several challenges. The main issues include limited transparency in information disclosure, inadequate accountability mechanisms, insufficient public and stakeholder participation, and suboptimal program effectiveness. Furthermore, weak inter-agency coordination and inadequate monitoring and evaluation systems hinder the achievement of the program's objectives. Therefore, continuous improvements in governance are essential through strengthened institutional coordination, enhanced transparency and accountability, and more effective monitoring mechanisms and public participation. These measures are expected to improve the efficiency, effectiveness, and sustainability of the Free Nutritious Meal Program, thereby ensuring that its intended social and public health objectives are successfully achieved.